ANALISIS UNJUK KERJA VENTURI VAKUM DENGAN VARIASI DIMENSI DAN VISKOSITAS FLUIDA - R.N. Akhsanu Takwim; Kris Witono (Universitas Lambung Mangkurat, 2018)
In the venturi vacuum, to produce a vacuum condition, a liquid fluid flow is required which is driven by a centrifugal pump through the venturi passage. The amount of vacuum pressure generated by venturi is influenced by the increase of flow velocity due to the diminution of the cross-section which follow Bernoulli principle. The flow velocity on the channel is influenced by the discharge generated by the pump following the continuity law. In addition to speed, channel input pressure is also a variable that affects venturi vacuum pressure. Performance of a setrifugal pump in the form of flow and pressure discharge greatly affect venturi vacuum performance, so that the variables affecting the performance of a setrifugal pump such as fluid viscosity, will also affect the venturi vacuum performance. Therefore, it is necessary to evaluate the effect of viscosity and venturi dimension on vacuum pressure and discharge into the main objective of this study so that the variables can improve the venturi vacuum pump performance. In this study liquid fluid with three variations of viscosity flowed through three different venturi dimension variations. Then measured parameters that occur, such as fluid flow fluid flow, fluid pressure fluid and vacuum pressure that occurs in the tube. From this study obtained, at the angle of diffuser 5o the lowest vacuum pressure of - 66.75 cmHg occurs in water fluid with viscosity of 17 centipoise. Similarly, at the angle of the diffuser 6.5o the value of the lowest vacuum pressure is also produced by a water fluid of -68 cmHg which is the lowest value compared to other diffuser angles and other fluid viscosities. While at 8o diffuser angle, the lowest vacuum pressure value is also produced by water fluid of -64.5 cmHg.